Cream crackers vs. “Maria” cookies: Which are the main differences? - Albuquerque, T.G. (2018)
Introduction: Cookies are widely consumed especially by young people. Nowadays there is a wide range of this type of products, and every day new options are available in the market. These foodstuffs are generally recognized as a source of unhealthy nutrients, such as salt and fat, namely saturated and trans fatty acids. The excessive intake of those nutrients is linked with an enhanced risk for the development of several chronic diseases. Aim: To determine salt, total fat and fatty acids composition of “Maria” cookies and cream crackers, as well as to estimate the benefit/risk associated with their consumption. Materials and methods: In 2016, 8 brands of cream crackers and 7 brands of “Maria” cookies widely distributed in the Portuguese market were selected to analyse the salt and fat contents and fatty acids composition. Sampling includes the main representative cookie brands, but also commercial and supermarket brands. Results and conclusions: For cream crackers the total fat content varied between 10.3 and 23.0 g/100 g, while for “Maria” cookies it ranged from 8.73 to 19.5 g/100 g. Concerning salt content, cream crackers have the highest value (1.82 g/100 g). The saturated fatty acids were the major in 6 cream cracker brands and in 4 “Maria” cookies brands. Trans fatty acids ranged from 29.2 to 82.4 mg/100 g (cream crackers) and from 24.5 to 73.2 mg/100 g (“Maria” cookies). The main difference between the studied groups was the salt content. Therefore, the reformulation of these foodstuffs is very important in order to produce healthier foods.